Legal Process for Banking Negligence in Violations of Customers' Privacy Rights and Personal Data - Pulubolo, Rifky; Thalib, Mutia Cherawaty; Ahmad, Ahmad (Universitas Negeri Gorontalo, 2024)
This research aims to find out and analyze the legal process for banking negligence in violating privacy rights and personal data.This research is classified as normative research with a statutory approach and a case approach. The research results show that personal data subjects have the right to sue and receive compensation for violations of the processing of personal data about themselves in accordance with statutory provisions. This is stated in Article 64 Paragraph (1) of Law no. 27 of 2022 concerning Personal Data Protection,